PERANCANGAN INTERIOR DIGITAL COWORKING SPACE SEBAGAI WUJUD DARI PROGRAM BANDUNG TEKNOPOLIS DENGAN PENDEKATAN BIOFILIK - Aflah, Dina; Wismoyo, Erlana Adli; Liritantri, Widyanesti (Telkom University, 2024)
The rapid development of information technology has made IT workers and digital startups increase in Indonesia. Indonesia is ranked 6th with the highest number of startups in 2022. With the growth of start-ups and the development of information technology, there is an increasing need for IT workers to support business development in Indonesia. Problems arise when investors want to invest in digital startups because local startups are not ready to receive large enough capital, so investors take initiatives to activate business incubator programs. Often, with the government's desire to accommodate the growth of the creative industry, namely by presenting the Bandung Teknopolis Program, the design of this Digital Coworking Space is expected to be present as a manifestation of this program. In addition, the concept of the Bandung Teknopolis program supports the creation of a Sustainability City, therefore the Biophilic concept is applied to the design. This concept is believed to be able to provide a sense of calm to the users of the space as well as improve the well-being of the users of the space in terms of both physical and mental as well as increasing work productivity.Keywords: Coworking Space, Bandung Technopolis, Biophilic